2002
DOI: 10.1097/00005053-200202000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Experiences of Japanese Inpatients With Chronic Schizophrenia

Abstract: Knowledge of the subjective experience of patients has important implications for the understanding and treatment of schizophrenia. However, previous studies examining the clinical correlates of subjective experiences have yielded inconclusive results. The present study of Japanese inpatients with chronic schizophrenia aimed to reveal the factorial structure of patients' subjective experiences and to examine the relationships between identified factors and demographic and clinical variables. A systematic asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…PRISMA study retrieval flow diagram. Forest plot of studies in the meta-analysis between motivation and clinician-rated negative symptom measures (k = 46) (Arbour-Nicitopoulos et al, 2014;Breitborde et al, 2014;Choi et al, 2012;Choi et al, 2016;DeRosse et al, 2014;Dowd et al, 2016;Duncan et al, 2016;Engel and Lincoln, 2016;Evensen et al, 2012;Fervaha et al, 2013b;Fervaha et al, 2014a;Fisher et al, 2017;Fiszdon et al, 2016;Fiszdon et al, 2017;Gard et al, 2014;Huang et al, 2016;Jang et al, 2016a;Jang et al, 2016b;Kako et al, 2014;Keefe et al, 2012;Kiang et al, 2003;Kim et al, 2016;Lincoln et al, 2016;Liraud et al, 2004;Llerena et al, 2013;Minyaycheva et al, 2017;Nakaya et al, 2002;Papsuev et al, 2015;Reddy et al, 2015a;Schlier et al, 2015;Takeda et al, 2017;Tas et al, 2012;Vinogradov et al, 2013;Wang et al, 2015;Yon and Loas, 2000). b Includes studies that were published as both a conference abstract and article.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…PRISMA study retrieval flow diagram. Forest plot of studies in the meta-analysis between motivation and clinician-rated negative symptom measures (k = 46) (Arbour-Nicitopoulos et al, 2014;Breitborde et al, 2014;Choi et al, 2012;Choi et al, 2016;DeRosse et al, 2014;Dowd et al, 2016;Duncan et al, 2016;Engel and Lincoln, 2016;Evensen et al, 2012;Fervaha et al, 2013b;Fervaha et al, 2014a;Fisher et al, 2017;Fiszdon et al, 2016;Fiszdon et al, 2017;Gard et al, 2014;Huang et al, 2016;Jang et al, 2016a;Jang et al, 2016b;Kako et al, 2014;Keefe et al, 2012;Kiang et al, 2003;Kim et al, 2016;Lincoln et al, 2016;Liraud et al, 2004;Llerena et al, 2013;Minyaycheva et al, 2017;Nakaya et al, 2002;Papsuev et al, 2015;Reddy et al, 2015a;Schlier et al, 2015;Takeda et al, 2017;Tas et al, 2012;Vinogradov et al, 2013;Wang et al, 2015;Yon and Loas, 2000). b Includes studies that were published as both a conference abstract and article.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Therefore, Kim et al stated that the important factors influencing insight were subjective suffering previously experienced by patients and how much such suffering was diminished by treatment. Nakaya et al8 also examined 129 inpatients with chronic-phase schizophrenia to establish the relationship between Subjective Experience of Deficits in Schizophrenia (SEDS), which was used in our study, and the question items related to insight (G12) in the Positive and Negative Syndrome Scale (PANSS);10 however, no significant correlation was observed. Such inconsistent findings may be attributed to differences in attributes of the patients studied (such as duration or stage of illness) and differences in the measures evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, subjective experience has been excessively overlooked in the symptomatic assessment of schizophrenia, because of the long-term emphasis on objective psychopathological evaluation and because of tenuous scientific evidence. Few studies have evaluated the relationship between the subjective experience of schizophrenia and insight 68…”
Section: Introductionmentioning
confidence: 99%
“…These experiences, if present, can be assessed in most affected subjects with the help of guided questioning [1,10]. Recent studies have shown that subjective experiences have important implications for early recognition of schizophrenia and related disorders [1,1114].…”
mentioning
confidence: 99%